Research on the Key Technologies of Parallel Operation for Full Power Wind Power Converter - LI Baoguo; CHEN Yanping; JIANG Yunfu; GAO Haiyou; LIU Min; LU Shengwen (Kongzhi Yu Xinxi Jishu)
It presented a design scheme of low voltage, large capacity, high power density and high reliability converter for direct drive full power wind power converter. Power modules were used in parallel to enlarge the capacity of single converter, dynamic circulation current between parallel modules was suppressed by reactor and a control algorithm of circulation current was adopted to reduce zero sequence current. At the same time, electrically isolation between two sets of three-phase windings of a six-phase permanent magnet synchronous motor was used to realize parallel connection between converters which solved the problems of circulating current between two back-to-back converters in parallel. Simulation and experimental results show that the converter can achieve a good mean current flow and circulation current suppression.